"Treading in sand": A qualitative study of the impact of austerity on inequalities in mental health. (17th October 2017) - Mattheys, Kate; Warren, Jonathan; Bambra, Clare
Abstract: Successive UK governments since 2010 have adopted policies of austerity characterized by public spending and social security cuts. There has been little qualitative research exploring the effects of these policies on inequalities in mental health. This article presents findings from a case study of Stockton‐on‐Tees, a local authority in the North East of England with exceptionally high spatial and socio‐economic inequalities. Qualitative interviews were undertaken with people experiencing mental health problems in different areas of the local authority, alongside interviews with key stakeholders. The findings offer an insight into spatial inequalities in people's lives, and the impact of deprivation on mental health. They suggest that austerity measures are having a damaging impact on individuals and communities in the most deprived areas of this unequal place, whilst leaving those from less deprived areas relatively unscathed—with the exception of increased job insecurity. The cuts in social security are impacting on health through both material and psychosocial pathways including increased financial hardship and chronic stress. The intrusion of the state into people's everyday lives was such that the notion of the "home as an asylum" was broken, giving many no respite from the draining day‐to‐day experiences of poverty. The findings are discussed in relation to the continuing program of welfare changes and public spending cuts in the United Kingdom, including avenues for further research and key recommendations for policymakers.